PISA tests in Latin America: results in context - Tiramonti, Guillermina (Avances en Supervisión Educativa, 2014)
The educational reforms implemented in Latin America in the ‘90s introduced changes in the modes of regulation of educational systems based on the adoption of mechanisms for assessing student achievement. Since 2000, eight Latin-American countries (Argentina, Chile, Uruguay, Colombia, Brazil, Costa Rica, Mexico and Peru) are involved in the PISA tests. The article presents a brief review of the social and educational situation of the Region, relevant for the interpretation and comparative analysis of the results of these tests that is presented below.